Strategies to optimize QTL detection designs in dairy sheep populations: The example of the Sarda breed - Casu S.; Carta A.; Elsen J.M. (Breeding programmes for improving the quality and safety of products. New traits, tools, rules and organization?, 2003)
This paper faces the problem of reducing costs of genotyping and recording traits not routinely measured in QTL detection programs for dairy sheep outbred populations. With this aim, starting from the actual population structure of the Sarda breed selection nucleus, QTL detection power of daughter design, granddaughter design, and alternative strategies as selective genotyping or selective phenotyping was calculated. Results were discussed focusing on global costs and practical implications of applying QTL detection designs in dairy sheep outbred populations.
Meeting of the Sub-Network on Genetic Resources of the FAO-CIHEAM Inter-Regional Cooperative Research and Development Network on Sheep and Goats, 2002/05/9-11, Sassari (Italy)